Factors associated with the progression of aortic valve calcification in older adults. (15th June 2023) - Leibowitz, David; Yoshida, Yuriko; Jin, Zhezhen; Nakanishi, Koki; Mannina, Carlo; Elkind, Mitchell S.V.; Rundek, Tatjana; Homma, Shunichi; Sacco, Ralph L.; Di Tullio, Marco R.
Abstract: Background: Aortic valve calcification (AVC) is a common valvular abnormality that predisposes to stenosis; AVC progression and factors associated with it remain unclear. We investigated the association of clinical factors and serum biomarkers with AVC progression in a population-based cohort of older adults. Methods: Participants enrolled in both the Cardiovascular Abnormalities and Brain Lesion study (CABL; years 2005–2010) and the Subclinical Atrial Fibrillation And Risk of Ischemic Stroke study (SAFARIS;2014–2019) represent the study cohort. AVC was defined as bright dense echoes >1 mm in size on ≥1 cusps; each cusp was graded on a scale of 0 (normal) to 3 (severe calcification) at baseline and follow up. Serum biomarkers were measured at the time of follow-up assessment. Results: 373 participants (mean 68.1 ± 7.6 years of age, 146 M/ 227F) were included. 139 (37%) had AVC progression;93 (25%) had mild progression (1 grade), and 46 (12%) had moderate-severe progression (≥2 grades). The only significant clinical predictor of any progression was the use of anti-hypertensive medication which was associated with older age, higher BMI and more frequent hypertension, diabetes and hyperlipidemia. In multivariable analysis including biomarkers, transforming growth factor beta 1 (TGF-β1) was significantly associated with both all and moderate-severe AVC progression. Conclusions: A significant number of elderly subjects with AVC show progression of their valve disease; individual vascular risk factors are not associated with AVC progression, although a combined effect may exist. Higher levels of TGF-β1 are observed in individuals with AVC progression. Graphical abstract: Unlabelled Image Highlights: Aortic valve calcification (AVC) is a common progressive valvular abnormality. We measured AVC in elderly subjects at baseline and after a mean 8 year follow up. Individual vascular risk factors are not associated with AVC progression. Higher levels of transforming growth factor beta in subjects with AVC progression.